Comprehensive study on the role of eco-friendly working fluid properties on ORC performances - Sarkar J. (My University, 2025)
In the present study, the effects of various low-Global Warming Potential (GWP) fluid properties on organic Rankine cycle (ORC) performances are examined for low grade heat sources and an attempt is made to prepare a general guideline to compare working fluids for ORC based on their basic properties. Theoretical study on ORC is conducted to study the effects of various fluid properties on net power generation, thermal efficiency, turbo-machinery and heat exchanger compactness. The considered eco-friendly working fluids for ORC were shortlisted based on operational, environmental and safety criteria. Performance comparison between selected working fluids shows that propane is the best fluid in term of compactness of turbo-machineries, whereas n-Pentane is the best fluid in terms of net power generation, thermal efficiency and heat transfer requirement. Study shows that the molar mass, normal boiling point temperature, critical temperature and phase diagram characteristics have significant effect on cycle performance indexes. However, the effect of properties does not show any common criteria for best in terms of all performance indexes. Finally, a flowchart based on the physical, chemical, thermal and environmental data is presented, which will be useful for comparison of fluids and selection for certain design targets.